On the Relationship Between Cognitive Ability and Risk Preference - Thomas Dohmen; Armin Falk; David Huffman; Uwe Sunde (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
This paper focuses on the relationship between cognitive ability and decision making under risk and uncertainty. We begin by clarifying some important distinctions between concepts and measurement of risk preference and cognitive ability and then take stock of what is known empirically on the connections between cognitive ability and measured risk preferences.
Keywords: 330